THE ROLE OF THE E-PRESCRIBING SYSTEM IN HEALTHCARE: A SYSTEMATIC REVIEW - Ayyoehan Tiara Annisa; Nanang Munif Yasin; Susi Ari Kristina (Jurnal Farmasi Sains dan Praktis, 2023)
The electronic prescribing system has a good role in health services with the powerful features that this system has, when compared to manual prescribing. This systematic review aims to determine the role of the electronic prescribing system in health services. The literature search was conducted from 21 November 2022 using PubMed, ProQuest, Google Scholar, ScienceDirect, Scopus, and Sage PUB as literature search area databases. A literature search strategy using BOOLEAN Operator to help specify the search terms. Literature search based on inclusion criteria. After eliminating duplication, title, abstract and full text, 8 articles were obtained for analysis. The electronic prescribing system has a good role in health services, including reducing medication errors, improving the quality of communication and information both between staff and staff and patients, shortening service time, having an alert system that is able to detect allergies, drug interactions, and adverse drug reactions. desired, time and cost efficiency, effectiveness in terms of patient safety, providing satisfaction for users because with these qualified features they can help in terms of service when compared to manual prescriptions. Further research should be conduct to review the role of Clinical Decision Support System and the electronic Health Record in healthcare due to its limitation.